Assessment of the risk of complications in bariatric surgery - L. I. Davletbaeva; K. A. Anisimova; D. I. Vasilevsky; S. G. Balandov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. Surgical treatment of obese patients includes a high risk of complications.Material and methods. The article presents the analysis of the informativeness and reliability of OS-MRS, E. Livingston, P. Turner scores in predicting postoperative complications in patients with overweight and metabolic disorders.Results. According to the study, the OS-MRS score was the most reliable.